Schumpeterian dynamics and financial market anomalies - Esther Merey; Horst Hanusch; Thomas Grebel (Universität Augsburg, Institut für Volkswirtschaftslehre, 2004)
In this paper we try to put together both the dynamics of the endogenous evolution of an industry and the corresponding dynamics on the capital market. The first module of our modelling efforts is the endogenous evolution of the industry based on the micro-behaviour of boundedly rational agents. They strive to undertake entrepreneurial actions and found new firms. Thereby, the role of knowledge diffusion is emphasized. The second module, the capital market module, will also be represented by boundedly rational agents. They read the data of the real side of the economy - induced by the real economy module - interact with other investors and eventually derive their investment decisions. The cognitive process will be modelled using a neural network approach.
urn:nbn:de:bvb:384-opus4-711901
Keywords: M13; G11; D84; O3; 330; neural networks; financial markets; entrepreneurship; endogenous evolution; Unternehmer; Unternehmensgründung; Wachstumsbranche; Wissenstransfer; Finanzmarkt; Risikokapital; Business Network; Neuronale Netze; Evolutionsökonomik; Theorie